3D modeling of the ownership structure of condominium units. (September 2016) - Li, Lin; Wu, Jindi; Zhu, Haihong; Duan, Xinqiao; Luo, Feng
Abstract: Existing studies on modeling immovable ownership have not explored the internal structure and internal semantic relations of the ownership of condominium units in depth. This paper suggests extending CityGML with legal concepts from the Land Administration Domain Model (LADM) via the application domain extension (ADE) mechanism of the CityGML as a feasible approach for describing the ownership structure of condominium units. Based on legislation in China, a CityGML–LADM ADE model is proposed to precisely present the ownership structure of a condominium unit, which reflects the interrelations of legal objects and their physical counterparts. Finally, the proposed model is validated by two case studies. Highlights: An ownership structure of a condominium is presented by mapping the physical parts and corresponding legal treatments. A CityGML-LADM Application Domain Extension (ADE) model is proposed for the ownership structure. The proposed three-dimensional model can express the ownership for a condominium in more detail than the current models do. This study also shows that ADE in CityGML is an effective tool to develop practical spatial models for land administration.